Improving the Quality of Electricity in Eastern Europe: Challenges and Solutions - Gheorghe E. Safta; Daniel N. Fita; Florin G. Popescu; Alin E. Cruceru; Razvan C. Olteanu; Adrian M. Schiopu; Gabriela Popescu (Scientific Research, New Technologies and Applications Vol. 9, 2024)
This paper explores the current challenges in electricity quality in Eastern Europe, focusing on factors such as reliability, stability, and efficiency. With the region’s energy sector undergoing significant transformation, from post-communist restructuring to the transition to renewable energy sources, the importance of ensuring high-quality electricity is paramount. The paper evaluates infrastructure inadequacies, grid modernization, regulatory changes, and the integration of renewable energy sources. Finally, it outlines potential strategies to improve power quality through technological innovation, investment, and cross-border cooperation.